EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK DISKUSI UNTUK MENINGKATKAN KONSEP DIRI SISWA KELAS XI - Julia Putri Fauziyah; Dida Firmansyah; Prio Utomo (IKIP Siliwangi, 2026)
This research was motivated by the low level of self-concept among some vocational high school students, which can negatively impact their personal development and future planning. The aim of this research was to determine the effectiveness of group counseling using discussion techniques in improving the self-concept of 11th-grade students at SMK Negeri Pertanian Pembangunan Lembang. The study employed a mixed-method approach with a sequential explanatory design, combining quantitative and qualitative methods. The quantitative component used a pre-experimental one-group pretest-posttest design. Results of the paired sample t-test showed a significant increase in self-concept after the group counseling was administered. The N-Gain score fell into the moderate category. Qualitative data obtained from observations and interviews supported the quantitative findings. These results indicate that the discussion technique in group counseling provides a reflective and supportive space that helps students to better understand and appreciate themselves. In conclusion, this service is effective in enhancing students’ self-concept and is recommended as a school-based intervention.